Principles of constructing gyroscopes based on photonic crystal (band-gap) fibers - Haider Ali Muse, Al-Sudani (Radiotekhnika, 2021)
The gyroscope is a device that makes it possible to measure the change in the orientation angles associated rotation of the body relative to an inertial coordinate system. Photonic crystal fiber gyroscopes are a kind of optical gyroscopes that offer many new features beyond that conventional fiber optic gyroscopes can offer. In any case, the properties of the optical fiber can play a large role in determining the characteristics of the gyroscope. The principle of operation of most optical gyroscopes is based on the Sagnac effect or the Sagnac interferometer, the essence of which is as follows. If two light waves propagate in a closed optical circuit in opposite directions, then in the case of an immovable circuit, the phase incursions of both waves that have passed the entire circuit in opposite directions will be the same. When the contour rotates around an axis normal to the contour plane, the phase incursions of the waves become unequal, and their difference in the general case will be proportional to the angular velocity of the contour rotation, the area covered by the contour, and the frequency of the electromagnetic wave (EMW). Since the area and frequency of the EMW remain unchanged during the operation of the gyroscope, the phase shift will be proportional only to the angular velocity. The use of photonic crystal fiber to increase the sensitivity is very promising; it significantly reduces the drift through thermal polarization, resistance, and the Kerr effect. This article suggests the use of photonic-crystal (hollow-core) fiber in optical gyroscope instead of conventional fibers.